2017
DOI: 10.1155/2017/2719752
|View full text |Cite
|
Sign up to set email alerts
|

Fitness Effects of 10-Month Frequent Low-Volume Ball Game Training or Interval Running for 8–10-Year-Old School Children

Abstract: We investigated the exercise intensity and fitness effects of frequent school-based low-volume high-intensity training for 10 months in 8–10-year-old children. 239 Danish 3rd-grade school children from four schools were cluster-randomised into a control group (CON, n = 116) or two training groups performing either 5 × 12 min/wk small-sided football plus other ball games (SSG, n = 62) or interval running (IR, n = 61). Whole-body DXA scans, flamingo balance, standing long-jump, 20 m sprint, and Yo-Yo IR1 childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
1
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 45 publications
2
35
1
6
Order By: Relevance
“…It was demonstrated in previous studies that after-school exercise programs with fitness emphasis are effective for improving physical fitness in children and adolescents ( Ara et al, 2006 ; Gutin et al, 2008 ; Carrel et al, 2011 ). Recreational team sports provide fun and effective options to encourage adolescents to improve their fitness profile ( Larsen et al, 2017 ; Cvetković et al, 2018 ; Hammami et al, 2018 ; Trajković et al, 2020a ). However, there was only limited positive fitness effects following frequent low-volume ball games and interval running in children aged 8–10 years ( Larsen et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was demonstrated in previous studies that after-school exercise programs with fitness emphasis are effective for improving physical fitness in children and adolescents ( Ara et al, 2006 ; Gutin et al, 2008 ; Carrel et al, 2011 ). Recreational team sports provide fun and effective options to encourage adolescents to improve their fitness profile ( Larsen et al, 2017 ; Cvetković et al, 2018 ; Hammami et al, 2018 ; Trajković et al, 2020a ). However, there was only limited positive fitness effects following frequent low-volume ball games and interval running in children aged 8–10 years ( Larsen et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recreational team sports provide fun and effective options to encourage adolescents to improve their fitness profile ( Larsen et al, 2017 ; Cvetković et al, 2018 ; Hammami et al, 2018 ; Trajković et al, 2020a ). However, there was only limited positive fitness effects following frequent low-volume ball games and interval running in children aged 8–10 years ( Larsen et al, 2017 ). On the contrary, greater improvements were found in physical fitness following recreational football intervention in children and adolescents ( Cvetković et al, 2018 ; Hammami et al, 2018 ; Trajković et al, 2020a ).…”
Section: Discussionmentioning
confidence: 99%
“…In physical education sessions based on SSGs, improvement in physical condition concerning internal load could be demonstrated compared with other training programs. For interval running [ 32 ], heart rate was recorded with a percentage of HRmax of 89.6 SSG, interval running with HRmax above 80%, and aerobic training above 90% of HRmax. These results are similar to those in our study and could demonstrate the importance of using SSGs to improve internal load fitness compared with other training programs such as interval running.…”
Section: Discussionmentioning
confidence: 99%
“…The integration of all training contents within a given microcycle is considered with overall performance in mind [ 12 ]. This additional physiological stress should be considered taking note of the other physical and technical/tactical sessions to avoid overload and optimize adaptation [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…School offers an opportunity to interact with most children and adolescents, and soccer is a part of the physical education (PE) curriculum of most grades in many countries around the globe. Several recent studies have shown that small-sided soccer games in school settings can improve the health profile of children and adolescents [ 13 16 ]. In these studies, both genders played together and marked improvements were found in both boys and girls.…”
Section: Introductionmentioning
confidence: 99%